RAMAN SPECTRAL CLASSIFICATION OF MINERAL- AND COLLAGEN-BOUND WATER’S ASSOCIATIONS TO ELASTIC AND POST-YIELD MECHANICAL PROPERTIES OF CORTICAL BONE - Unal, Mustafa (Bone, 2015)
Water that is bound to bone’s matrix is implied as a predictor of fracture resistance; however, bound water is an elusive variable to be measured nondestructively. To date, the only nondestructive method used for studying bone hydration status is magnetic resonance variants (NMR or MRI). For the first time, bone hydration status was studied by short-wave infrared (SWIR) Raman spectroscopy to investigate associations of mineral-bound and collagen-bound water compartments with mechanical properties. Thirty cortical bone samples were used for quantitative Raman-based water analysis, gravimetric analysis, porosity measurement, and biomechanical testing. A sequential dehydration protocol was developed to replace unbound (heat drying) and bound (ethanol treatment) water in bone. Raman spectra were collected serially to track the OH-stretch band during dehydration. Four previously identified peaks were investigated: I(3220)/I(2949), I(3325)/I(2949) and I(3453)/I(2949) reflect status of organic-matrix related water (mostly collagen-related water) compartments and collagen portion of bone while I(3584)/I(2949) reflects status of mineral-related water compartments and mineral portion of bone. These spectroscopic biomarkers were correlated with elastic and post-yield mechanical properties of bone. Collagen-water related biomarkers (I(3220)/I(2949) and I(3325)/I(2949)) correlated significantly and positively with toughness (R(2)=0.81 and R(2)=0.79; p<0.001) and post-yield toughness (R(2)=0.65 and R(2)=0.73; p<0.001). Mineral-water related biomarker correlated significantly and negatively with elastic modulus (R(2)=0.78; p<0.001) and positively with strength (R(2)=0.46; p < 0.001). While MR-based techniques have been useful in measuring unbound and bound water, this is the first study which probed bound-water compartments differentially for collagen and mineral-bound water. For the first time, we showed an evidence for contributions of different bound-water compartments to mechanical properties of wet bone and the reported correlations of Raman-based water measurements to mechanical properties underline the necessity for enabling approaches to assess these new biomarkers noninvasively in vivo to improve the current diagnosis of those who may be at risk of bone fracture due to aging and diseases.